If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -29 = 43 Reorder the terms: -29 + 8x = 43 Solving -29 + 8x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 8x = 43 + 29 Combine like terms: -29 + 29 = 0 0 + 8x = 43 + 29 8x = 43 + 29 Combine like terms: 43 + 29 = 72 8x = 72 Divide each side by '8'. x = 9 Simplifying x = 9
| +9+7(4)(-2)(-1)= | | x/4 | | x/4-3 | | 2x-5+3x-10=15 | | 1.4+.3x=.6x-3.1 | | -9(5)(+3)+8-2(6)= | | -1.6r=4 | | -5x=40+3x | | x+1/x=6 | | p+0.03p=113.3 | | .35p-1.5=9 | | 9x*-3x-2=0 | | 3(-6)(-4)-7-5= | | 2(x-5)=3(x+10) | | .35-1.5=9 | | -4y=-3x-18 | | -3(2x-5)-4(x+7)=0 | | m/8+3=16 | | -.35p-1.5=9 | | 7xy-2xz+4xz-12xyz+2zx=0 | | r/14=-23/14 | | 15x-4=9x+23 | | 3x-7=2x+10 | | 2w+2(2w+10)=30 | | 3y/7=5y+6 | | 2-3a+8a-12=7a+4*4 | | 6x+18=10x-2 | | -(3k+4)=6k-4(3k+2) | | -x-2=-2x+12 | | 7x+5=6x-6 | | -x-6=3x-6 | | 14=-3+5 |